Critical toponomy Place names in political, historical and commercial landscape - Beyer, Herman; Raper, Peter; Brenzinger, Matthias; du Plessis, Theodorus (UJ Press, 2019)
Critical Toponymy: Place names in political, historical and commercial landscapes contains a selection of double-blind peer-reviewed papers from the 4th International Symposium on Place Names that took place 18-20 September 2017 in Windhoek, Namibia. These papers present current thinking on how the critical turn in social sciences is manifested in toponymic research, not only locally but also internationally. As such it includes research on place names from South Africa, Namibia, Zimbabwe, Austria, Slovenia, Central America and even the former Czechoslovakia. The contributions show that the etymology of place names are never purely linguistic - social, political, commercial and other factors influence the giving, use and adaptations of these linguistic and cultural artefacts. Furthermore, given their high symbolic content, place names also serve as political and commercial currency. Place names are therefore important symbolic markers in preserving or changing cultural identities, and in marking or facilitating socio-political changes and relations. Critical Toponymy showcases the many ways in which the representational potential of place names can be deployed in different contexts. Scholars as well as practitioners in toponymy and sociolinguistics will find this an illuminating read.